2020
DOI: 10.1038/s41392-020-00348-8
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint molecules in natural killer cells as potential targets for cancer immunotherapy

Abstract: Recent studies have demonstrated the potential of natural killer (NK) cells in immunotherapy to treat multiple types of cancer. NK cells are innate lymphoid cells that play essential roles in tumor surveillance and control that efficiently kill the tumor and do not require the major histocompatibility complex. The discovery of the NK’s potential as a promising therapeutic target for cancer is a relief to oncologists as they face the challenge of increased chemo-resistant cancers. NK cells show great potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 306 publications
(309 reference statements)
0
70
0
1
Order By: Relevance
“…In the tumor microenvironment, different immune cells confer different tumor responses. T-helper-1 cells, natural killer cells, M1 phenotype macrophages, and DC1 phenotype dendritic cells are involved in the suppression of tumorigenesis and development, while T-helper-2 cells, M2 macrophages, DC2 dendritic cells, and regulatory T cells (Treg) suppress immune responses [ 43 45 ]. Analysis of the unique properties of immune cells in the tumor microenvironment may inform the design of cancer immunotherapy targets.…”
Section: Discussionmentioning
confidence: 99%
“…In the tumor microenvironment, different immune cells confer different tumor responses. T-helper-1 cells, natural killer cells, M1 phenotype macrophages, and DC1 phenotype dendritic cells are involved in the suppression of tumorigenesis and development, while T-helper-2 cells, M2 macrophages, DC2 dendritic cells, and regulatory T cells (Treg) suppress immune responses [ 43 45 ]. Analysis of the unique properties of immune cells in the tumor microenvironment may inform the design of cancer immunotherapy targets.…”
Section: Discussionmentioning
confidence: 99%
“…Very recent data have shown that ICIs can act not only on T cells but also on NK cells, which express several ICs that inhibit their cytotoxic function, such as PD-1, TIM3, TIGIT, LAG-3 and CD96 ( 184 ). Several clinical trials are ongoing investigating the effects of ICIs on NK cells in different solid cancers, as reviewed in ( 185 ).…”
Section: Strategies To Revert Immune Suppression and Improve Cancer Imentioning
confidence: 99%
“…The suppression of MDSCs by anti-CSF-1R neutralizing antibodies or small molecule inhibitors has been shown to reduce tumor growth and metastasis ( Noy and Pollard, 2014 ; Szebeni et al, 2016 ; Ridker et al, 2017 ). Immune checkpoint molecules in NKs were also reported to be potential targets for immunotherapy ( Cao et al, 2020 ). To date approximately 174 clinical trials involving CTLA-4 and 750 involving PD-1 and its receptor PD-L1 have been reported (as reviewed in Boohaker et al, 2018 ; Darvin et al, 2018 ; Chen T. et al, 2019 ).…”
Section: Targeting the Tumor Microenvironment For Therapymentioning
confidence: 99%